A practical guide for understanding online business models. Issue 1 (19th November 2018) - Kim, Won
Abstract : Purpose: There is a lack of clarity about what online business models are. The top 20 Google search results on online business models are articles that explain online business models. However, each of them deals with just one or two elements of business strategies. The list of business models is also a mixture of business strategies. This paper aims to provide practical guide that puts these business models into proper perspective. Design/methodology/approach: A business model includes all key elements of the business, marketing and operational strategies. There are many such elements. The author has reviewed the popular use of the term online business models and found that just five of the key elements can put almost all of them into proper perspective. Findings: Five elements of the business and marketing strategies constitute a practical guide for understanding, discussing and even designing the first working draft of a business plan. Practical implications: The practical guide will serve as a robust vehicle for understanding, discussing and even designing the first working draft of a business plan. The current haphazard use of the term online business models does not shed light on online business models. Originality/value: The author has examined 20 top Google search results for "online business models" and "business models". These are articles that talk about 3-17 "business models". The author examined all of them and confirmed that the five key elements of the business and marketing strategies can put all of them into proper perspective.